Crowdsourcing good landmarks for in-vehicle navigation systems. Issue 10 (2nd October 2016) - Large, David R.; Burnett, Gary; Benford, Steve; Oliver, Keith
ABSTRACT: Augmenting navigation systems with landmarks has been posited as a method of improving the effectiveness of the technology and enhancing drivers' engagement with the environment. However, good navigational landmarks are both laborious to collect and difficult to define. This research aimed to devise a game concept which could be played by passengers in cars, and would collect useful landmark data as a by-product. The paper describes how a virtual graffiti tagging game concept was created and tested during on-road trials with 38 participants. The data collected in the road trials were then validated using a survey, in which 100 respondents assessed the quality of the landmarks collected and their potential for reuse in navigation applications. Players of the game displayed a consensus in choosing where to place their graffiti tags, with over 30% of players selecting the same object to tag in 10 of the 12 locations. Furthermore, significant correlation was found between how highly landmarks were rated in the survey and how frequently they were tagged during the game. The research provides evidence that using crowdsourcing games to collect landmarks does not require large numbers of people, or extensive coverage of an area, to produce suitable candidate landmarks for navigation.